Have the educational reforms worked in Latin America? A case study of Argentina, Brazil and Chile - Cristian G Perez Centeno; Mariana Leal (Arizona State University, 2011)
Almost ten years after the political closing of the neoliberal cycle that framed educational reforms in Latin America in the 90s, this paper assesses their success in three countries - Argentina, Brazil and Chile. The analysis is supported by the theoretical framework developed by Martin Carnoy in his text 'Are educational reforms working in Latin America? New perspectives' (2002) and spin-off texts, as an alternative model to classical analysis of educational reforms and quality assurance of its various educational systems. As regards methodology, several indicators, weighted by Carnoy for consideration of success of Latin American reforms, will be used to analyze educational systems of Argentina, Brazil and Chile: (a) expansion of system access, (b) performance of the most disadvantaged intake and (c) improvement of factors associated to educational achievement. Data focus, mainly, on secondary school education since it is at this stage that the greatest difficulty is encountered. Primary education coverage is practically universal and diminishes rapidly when secondary education is considered.  In its analysis, this study compares not only the impact of reforms within and across the countries mentioned above but also on Carnoy's proposal for analysis and traditional models of reform assessment (basically, through the study of changes in effectiveness -learning results- and internal efficiency of systems - repeat students and drop-outs). Finally, this paper raises questions about the true capacity for improvement that reform processes have had for the population of those countries -specially for Argentina- not just in educational terms but also with respect to its democratization and, considering the Conference theme: decrease in vulnerability, injustice and inequity.